Growing Black food on sacred land: Using Black liberation theology to imagine an alternative Black agrarian future. (October 2021) - McCutcheon, Priscilla
This article uses Black liberation theology (BLIBT) as a framework to theorize "the spirit" in the alternative food and sustainable agriculture movement. While BLIBT was formally named by theologian James Cone, it was born of the struggles of Black people in the United States who believed that God called Black people to be free, and God called Black preachers to preach Black liberation. I argue that Black liberation is a grounded vantage point to understand how some Black people might find freedom through food and agriculture. In the first potion of the paper, I make a claim for the importance of studying spirituality in agrarian and food spaces, whether or not a researcher is spiritually inclined. In the second portion of the paper, I delve deeper into Cone's articulation of BLIBT, and explore how we might begin to theorize it as an agrarian mandate including: a call for an urgent food source, liberation of the individual Black body, community ownership of land, the spirit of Black religious spaces, an emphasis on land reparations, and the freedom to dream. I conclude with a call for why an attention to BLIBT is called for in our present moment.